Relationship Between Physical Fitness and Body Composition of Adolescent 6 Volleyball Athletes (Fiep Bulletin - online, 2025)
The study aimed to verify the relationship between physical fitness and body composition of volleyball athletes, adolescents between 15 and 16 years old, from the Joinville region, Santa Catarina. The study population consisted of 25 base athletes from AVOJOI from the Joinville/SC region, all male players aged 15 and 16 years old. The physical fitness variables were: 1) Vertical Jump, 2) Horizontal Jump, and 3) Speed; and the body composition variables were: 1) Body Mass Index (BMI kg/m²) and 2) Fat Percentage (%G). The information analyzed in the R Studio software, where the data were compared using One-Way ANOVA to verify significant differences in the variables. The results showed that BMI (kg/m²) has a significant effect (p=0.011) on Speed values (3.55±0.18), revealing a significant difference between the “Normal” and “Overweight” classifications (p=0.010). Likewise, %F has a significant effect on Horizontal (p=0.036) and Vertical (p=0.012) Jump values, revealing a significant difference between the “Excellent” and “Moderately High” classifications (p
Keywords: Volleyball; Physical Fitness; Body Composition; Adolescents